2012
DOI: 10.1002/path.4002
|View full text |Cite
|
Sign up to set email alerts
|

The peritoneal tumour microenvironment of high‐grade serous ovarian cancer

Abstract: High-grade serous ovarian cancer (HGSC) disseminates early and extensively throughout the peritoneal space, causing multiple lesions that are a major clinical problem. The aim of this study was to investigate the cellular composition of peritoneal tumour deposits in patient biopsies and their evolution in mouse models using immunohistochemistry, intravital microscopy, confocal microscopy, and 3D modelling. Tumour deposits from the omentum of HGSC patients contained a prominent leukocyte infiltrate of CD3+ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 24 publications
0
52
0
Order By: Relevance
“…The angiogenic switch (or initiation of angiogenesis) is a discrete step in tumor development that is required to ensure exponential tumor growth. We have shown this step occurs after leukocyte recruitment to the tumor deposits in the ID8 model (25). Interestingly, we observed a reduction in vascular endothelial growth factor A (VEGFA) and Angiopoietin 2 (Ang-2) expression in both IL-17 −/− and TCRδ −/− mice compared with WT controls (Fig.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The angiogenic switch (or initiation of angiogenesis) is a discrete step in tumor development that is required to ensure exponential tumor growth. We have shown this step occurs after leukocyte recruitment to the tumor deposits in the ID8 model (25). Interestingly, we observed a reduction in vascular endothelial growth factor A (VEGFA) and Angiopoietin 2 (Ang-2) expression in both IL-17 −/− and TCRδ −/− mice compared with WT controls (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…This time point, which coincided with tumor growth arrest in IL-17 −/− mice (Fig. 2F), approximately corresponds to the so-called "angiogenic switch" in the ID8 model (25). The angiogenic switch (or initiation of angiogenesis) is a discrete step in tumor development that is required to ensure exponential tumor growth.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…These processes are dependent on cytokines, extracellular matrix proteins, growth factors, proteolytic enzymes, and inflammatory cells [4,[6][7][8][9][10]. Ultimately, angiogenesis and tumor neovascularization herald cancer growth and dissemination.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Animal models illustrate the ability of intra-peritoneal OC cells to attach to avascular areas, subsequently forming vascular deposits, with rich infiltrates containing lymphocytes, macrophages, fibroblasts, and pericytes [9]. Additional studies have shown that angiogenesis is essential for tumor invasion and metastasis, and is required for tumor growth beyond 1-2 mm [11,12].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%